Energy-Saving Methods of Operating Asynchronous Motors - Mirzaliev Bobur Batiyorvich (International Journal on Orange Technologies, 2022)
When the engine is started, in some mechanisms its speed is required to increase very evenly over a period of time, and in others the starting torque is required to be much greater. In order for the engine to be easily started, its starting torque must be large enough, and the starting current must be as small as possible.